PENGARUH KINERJA CORPORATE SOCIAL RESPONSIBILITY TERHADAP PERSISTENSI LABA PADA SEKTOR PERTAMBANGAN - Viena Yuana (Business Accounting Review, 2016)
The majority of previous studies have examined the affect of Corporate Social Responsibility (CSR) on periodic financial performance. So far there were still very few studies that had examined the affect of Corporate Social Responsibility (CSR) on earning persistence. In fact, these studies had not been done in the mining sector. The aim of this study was to examine the affect of CSR on earning persistence in mining sector in Indonesia by using control variables consisting of operating cycle, sales volatility, cash flow volatility, proportion of negative earnings, competition intensity, and firm size.The data in this study were processed by using SPSS version 22. The samples used in this study were 60 observations in the mining sector that were listed in Indonesian Stock Exchange in the period of 2010-2014. This study had not been able to prove that CSR was beneficial in generating persistent earnings. Moreover, among of the control variables, only proportion of negative earnings that proved has negative affect on earnings persistence.